(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Indian industry hasentered a new phase in its development. In many sector of the industry such asmachine tools, textile machinery, power equipment’s, material handlingequipment etc., the industry is in a position to plan for major initiativeseven on an international basis. The country has the four advantages in terms ofcheaper labour cost, as also abundant availability of well-trained engineersand experienced managers and technical labour force, scientists, etc. theseaspects are likely to receive adequate attention in the present decade. Thecountry has been opened up to the forces of globalization. With globalization,they are more exposed to severe competition both from large-scale sector,domestic, foreign and from the MNCs. The entrepreneur is the key to thecreation of new enterprises that energies the economy and rejuvenate theestablished enterprises that make up the economic structure. Entrepreneurship is emerging as an important avenue ingaining economic independence for women. In last two decades (inpost-liberalization era), the economic reforms coupled with loosening of socialrestrictions has further provided an impetus to women to become entrepreneurs.According to the current trends most of the emerging women entrepreneurs are insmall and micro enterprises. A cursory look at their situation highlights a number ofmajor challenges faced by them. These challenges can be broadly classified as:lack of awareness, lack of information, difficulty in accessibility of finance,lack of easy access of entrepreneurial training and post training support, lackof market and network support, lack of self-confidence and managerial skillsetc. In recent times, the government has realized theimportance of entrepreneurship as a prominent alternative to traditional wageemployment in the new economy, and its role in increasing the pace of economicgrowth. Therefore, Indian government has come up with various special policymeasures to help women entrepreneurs. However, there are major limitations among womenentrepreneurs in accessing those facilities. These limitations arise due tovarious factors, such as: bureaucratic hassles, limited number of governmenttraining centres, lack of transportation mainly in remote areas, restriction ofgovernment officials in terms of timing when women also have to performhousehold activities etc.